PHARMACOGNOSTIC AND PRELIMINARY PHYSICO-CHEMICAL EVALUATION OF MATSYAKSHI [ALTERNANTHERA SESSILIS (LINN.) R.Br] - V T, *Dhanya; Eapen, Jollykutty (International Journal of Ayurveda and Pharma Research, 2017)
Alternanthera sessilis (Linn) R.Br. is a plant that belongs to the family Amaranthaceae. This species has a huge global range, including both native and introduced distribution. The plant has been widely used by the ethnic population for food and medicine. The plant has been mentioned in Ayurvedic classics by the name Matsyakshi. The plant is also observed to be an ingredient in the some of the formulations indicated for urinary system pathologies, in Chikitsamanjari, Yogamruta and some other traditional Ayurvedic texts in Kerala. The quality control of herbal crude drugs and their bioconstituents is of paramount importance in justifying their acceptability. The crude drugs can be identified systematically on the basis of their morphological, histological, chemical, physical and biological studies. The aim of the study is to evaluate the preliminary pharmacognostical and phytochemical evaluation of Alternanthera sessilis (Linn) R.Br. Pharmacognostical evaluation of the plant Alternanthera sessilis (Linn.) R.Br. was done by studying the macroscopic and microscopic features of leaf, stem and root of the plant. The preliminary phytochemical analysis including quantitative data, qualitative chemical analysis, Thin Layer Chromatography, High Performance Thin Layer Chromatography and Atomic Absorption Spectroscopy were determined. Various pharmacognostic and preliminary phytochemical characters observed in this may help in standardization, identification and carrying out further research in Alternanthera sessilis (linn.)R.Br.